Harnessing Guanidinium and Imidazole Functional Groups: A Dual-Charged Polymer Strategy for Enhanced Gene Delivery - Mapfumo, Prosper P.; Reichel, Liên S.; Leer, Katharina; Egger, Jan; Dzierza, Andreas; Peneva, Kalina; Fischer, Dagmar; Traeger, Anja (ACS Macro Letters, 2024)
Histidine and arginine are two amino acids that exhibit beneficial properties for gene delivery. In particular, the imidazole group of histidine facilitates endosomal release, while the guanidinium group of arginine promotes cellular entry. Consequently, a dual-charged copolymer library based on these amino acids was synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization. The content of the N-acryloyl-l-histidine (His) monomer was systematically increased, while maintaining consistent levels of methyl N-acryloyl-l-argininate hydrochloride (ArgOMe) or N-(4-guanidinobutyl)acrylamide hydrochloride (GBAm). The resulting polymers formed stable, nanosized polyplexes when complexed with nucleic acids. Remarkably, candidates with increased His content exhibited reduced cytotoxicity profiles and enhanced transfection efficiency, particularly retaining this performance level at lower pDNA concentrations. Furthermore, endosomal release studies revealed that increased His content improved endosomal release, while ArgOMe improved cellular entry. These findings underscore the potential of customized dual-charged copolymers and the synergistic effects of His and ArgOMe/GBAm in enhancing gene delivery.
CRIS-Team Scopus Importer:2024-08-02